Examining macroeconomic factors and environmental sustainability: An OLS regression analysis of the impact of exports, imports, governmental budget, and oil products on CO2 emissions in Jordan - Atyeh, Mohamad; Damrah, Sadeq (Edelweiss Applied Science and Technology, 2024)
This study aims to investigate the relationship between macroeconomic factors and CO2 emissions. The study used a sample of data covering the period from 1991 to 2019 and employed ordinary least squares (OLS) method to estimate the relationship. The study found that there is a strong relationship between CO2 emissions and the macroeconomic factors of exports, imports, governmental budget, and oil products. The R-squared value of 0.717668 suggests that these variables explain approximately 72% of the variation in CO2 emissions. The coefficients for exports, imports and oil products are statistically significant at the 5% level. A negative coefficient for exports indicates that an increase in exports is associated with a decrease in CO2 emissions. On the other hand, a positive coefficient for imports suggests that an increase in imports is associated with an increase in CO2 emissions. Additionally, the positive coefficient for oil products indicates that an increase in oil product consumption is associated with a significant increase in CO2 emissions. The coefficient for the government budget variable is not statistically significant, which suggests that changes in the government budget do not have a significant impact on CO2 emissions. The results are robust and reliable as the assumptions of linearity, normality and homoscedasticity of errors were met. The study results could help policy makers in taking potential actions to mitigate CO2 emissions in the country.